Brugada Pattern in a Child with Severe SARS-CoV-2 Related Multisystem Inflammatory Syndrome - Angelica De Nigris; Angela Pepe; Giangiacomo Di Nardo; Antonietta Giannattasio; Annamaria Pagano; Carolina D'Anna; Stefania Muzzica; Selvaggia Lenta; Giovanni Maria Di Marco; Vincenzo Tipo (MDPI AG, 2021)
This report presents the first case of Brugada pattern complicated by a supraventricular arrhythmia in a child with SARS-CoV-2 related Multisystem Inflammatory Syndrome in Children (MIS-C). A 7-year-old boy came to our Emergency Department with 7 days of abdominal pain and fever. MIS-C was diagnosed on the basis of the clinical, laboratory and instrumental tests. On admission, ECG showed type 1 Brugada pattern in the right precordial leads. During hospitalization the onset of supraventricular arrhythmias complicated the clinical picture. This case underlines management complexity of supraventricular arrhythmic events, different from atrial fibrillation, in patients with Brugada pattern in the context of a systemic inflammatory condition with significant cardiac involvement. All potential therapeutic choices should be considered to ensure the best outcomes.